Working with Infrastructural Communities: A Material Participation Approach to Urban Retrofit. (March 2021) - Johnson, Charlotte; Bell, Sarah; Borrion, Aiduan; Comber, Rob
Retrofit is a rising area of concern for Science and Technology Studies (STS) scholars of infrastructure. This paper sits at the junction between applied and theoretical approaches by using STS to support interventions in urban infrastructure systems and expand STS critique of retrofit. It discusses findings from a multidisciplinary project piloting retrofit possibilities to positively impact the way water, energy, and food resources were consumed in a London housing estate. Through qualitative research, we found that residents were making social and material interventions in infrastructure systems to manage the way resources were consumed at home, driven by a commonly held motivation to avoid wastefulness. We then mapped the social and material factors that helped or hindered these individual ambitions and used them to inform our codesign process. We found it helpful to think of the residents as an infrastructural community; a group of residents that share a material connection that can help mobilize collective action on shared consumption. We suggest this concept is useful for interventions and critiques of infrastructure retrofit, particularly in cities in the Global North where retrofit programs aim to rescale national systems to neighborhood levels. The concept highlights the possibilities for participation that emerge from bottom-up retrofit.